Embrittlement of Poly(butylene terephthalate) Induced by Injection Molding Process. Issue 1 (21st October 2022) - Loyer, Camille; Régnier, Gilles; Duval, Vincent; Richaud, Emmanuel
Abstract: Poly(butylene terephthalate) (PBT) dumb‐bell samples are injection molded. Tensile tests reveal a brittle behavior for samples manufactured at high temperature (280°C) and long residence times contrarily to those processed at 240°C and 260°C with moderate residence times. Average weight molar mass and DSC measurements are exploited to derive an embrittlement criterion. The comparison with some literature data suggests that samples are mainly degraded by a thermolysis process with minor effect of oxygen.